Perbedaan Pemberian ASI Eksklusif Antara Ibu Rumah Tangga dengan Ibu yang Bekerja di Luar Rumah di BPS Umu Hani Bantul Tahun 2011 - Dyah Kartika Sari; Prasetya Lestari; Nining Sulistyawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Based on World Health Organization (WHO), The cause of 54% mortality baby in the world is inﬂ uenced by nitrition factors including affected by granting breast-feeding. Tendency of the use breast feeding in some society is declining. This is due to paradigm shifting in any women because of growing understanding women about self-actualisazion. This research aims to compare providion of exclusive breastfeeding between working mothers and household mothers at BPS Umu Hani Bantul. This observational study used cross-sectional design with consecutive sampling. Data were obtained by using questionnaire and analysed through table a frequency distribution subjects and data statistic was tested by using chi-square. The result were 84% breastfeeding mothers at BPS Umu Hani as housewife, 15.9% of those working outside and at about 68,2% given exclusive breastfeeding. There was signiﬁcantly distinctive at about p< 0,05 on the proportion of exclusive breast-feeding given by household mothers and housewife mothers.